Effect of autologous platelet-rich plasma in the promotion of healing of chronic ulcers - Raslan, Mohamed M.; Milad, Nader M.; Abd AlAziz, Ahmed (International Surgery Journal, 2017)
Background: Chronic ulcers are a big health problem worldwide. Having a great impact at personal, social and professional levels. The use of autologous Platelet Rich Plasma (PRP) is a major advance in the treatment of these ulcers as an easy and cost-effective method. Platelets provide numerous growth factors enhancing tissue healing. The aim of this study was to evaluate the safety and efficacy of autologous platelet-rich plasma as a treatment of chronic non-healing ulcers. Methods: Autologous PRP was prepared from whole blood by centrifugation and activated by 10% calcium chloride. Twenty-Four (24) patients with non-healing ulcers of different etiologies, whom they met our inclusion criteria, were treated with PRP injected every two weeks locally into their wounds until healing. The ulcer dimensions were measured every week. The follow-up period was 12 weeks after healing. Results: The mean age of the study population 41±21 years. Complete healing was achieved in all patients. The mean rate of healing (average decrease in ulcer dimensions) was 0.48 cm/week. The rate of healing was greater at the week following injection. The mean time for healing was 6.11 weeks. Conclusions: Author witnessed the useful effects of PRP application on enhancing wound healing. The results from our case series showed that PRP is a safe and effective treatment for the promotion of healing chronic ulcers. Further research and controlled, randomized prospective clinical trials on larger patient population are important to validate our results.